Variations in adverse pregnancy and birth outcomes among Latin American and Caribbean-Born birthing people by region of origin, California birth cohort, 2007–2020 - Salma Iraqi; Shira Goldenberg; Rebecca J. Baer; Hector Lemus; Gretchen Bandoli (BMC Pregnancy and Childbirth)
Abstract Background Although many studies have highlighted better pregnancy and birth outcomes among foreign-born Latinas than among U.S.-born people, few have assessed heterogeneity in outcomes disaggregated by region of origin. We examined adverse pregnancy and birth outcomes among birthing people born in Latin America and the Caribbean (LAC) compared to people born in the U.S. Methods We used a retrospective cohort from the Study of Outcomes in Mothers and Infants compiled from California births (2007–2020). We examined descriptive statistics, unadjusted, and adjusted odds ratios for the association between LAC nativity and region of origin (versus U.S.-born) and preeclampsia, gestational diabetes, preterm birth, and small for gestational age. We also assessed the potential mediating roles of education, health insurance, and prenatal care. Results The sample included 5,917,974 infants, with 3,555,173 born to U.S.-born birthing people, and 1,385,679 born LAC-born birthing people, with the vast majority being from Mexico (82%) and Central America (14%). The odds of each outcome among those from LAC regions were lower relative to U.S.-born individuals, with the following exceptions. The adjusted odds of gestational diabetes was higher among those born in Mexico (13.3% vs. 8.0%, AOR: 1.6, 95% Cl: 1.6–1.6) and Central America (11.1% vs. 8.0%, AOR: 1.3, 95% Cl: 1.3–1.3) compared to those born in the U.S. The adjusted odds of preterm birth was higher for those born in the Caribbean (8.5% vs. 7.2%, AOR: 1.1, 95% CI: 1.0-1.2) and Central America (8.0% vs. 7.2%, AOR: 1.1, 95% CI: 1.1–1.1) compared to the U.S. Similarly, the adjusted odds of small for gestational age were higher for those born in the Caribbean (10.5% vs. 9.2%, AOR: 1.2, 95% CI: 1.2–1.3) and Central America (10.4% vs. 9.2%, AOR: 1.2, 95% CI: 1.2–1.2). Education and health insurance were identified as mediators of the associations. Conclusion There is significant heterogeneity in adverse pregnancy and birth outcomes among those born in LAC by region of origin, specifically among people from Mexico, Central America, and the Caribbean. These findings highlight the importance of assessing disaggregated data to address the distinct pregnancy and birthing needs of diverse foreign-born birthing people.